Nucleophilic Reactivities of 2‐Substituted Malonates1. Issue 10 (11th March 2016) - Puente, Ángel; He, Shanshan; Corral‐Bautista, Francisco; Ofial, Armin R.; Mayr, Herbert
Abstract: Kinetics of the reactions of 2‐substituted malonate anions and 5‐substituted Meldrum's acid anions with benzhydrylium ions and structurally related quinone methides have been monitored in dimethyl sulfoxide solution at 20 °C. The resulting second‐order rate constants followed the correlation lg  k (20 °C) = s N ( E + N ), which allowed the nucleophile‐specific parameters N and s N to be calculated for these highly stabilized carbanions and to integrate them in our comprehensive nucleophilicity scale. Given that the reactions of the benzhydrylium ions with the anions derived from 5‐aryl‐substituted Meldrum's acids did not proceed to completion, the corresponding equilibrium constants could be determined. In combination with available data for pyridines and benzoate ions, these equilibrium constants provide a direct comparison of the strengths of C‐, N‐, and O‐centered Lewis bases with respect to C‐centered Lewis acids. Abstract : The nucleophilic reactivities of 2‐substituted ethyl malonate anions and 5‐aryl‐substituted Meldrum's acid anions have been measured by using the benzhydrylium methodology. Additionally, the Lewis basicities ( LB ) of 5‐aryl‐substituted Meldrum's acid derivatives were determined, which provide a comparison of the strengths of C‐, N‐, and O‐centered Lewis bases towards a series of C‐centered Lewis acids.